Energy, exergy, economic and environmental (4E) analyses based comparative performance study and optimization of vapor compression-absorption integrated refrigeration system. (November 2015) - Jain, Vaibhav; Sachdeva, Gulshan; Kachhwaha, Surendra Singh
Abstract: Present work compares the performance of commercially available 170 kW vapor compression chiller with equivalent three configurations (parallel, series and combined series-parallel) of VCAIRS (vapor compression-absorption integrated refrigeration system) based on combined energy, exergy, economic and environmental (4E) analyses. Parallel, series and combined series-parallel configurations reduces the energy (electricity) consumption in the compressor by 50%, 76.8% and 88.3% respectively and consequently, reduce the significant amount of CO2 emission. Comparative exegetic analysis based on modified Gouy–Stodola law was performed which predicted higher irreversibility rate as compared to conventional approach. The thermoeconomic study shows that annual cost of the plant operation is 13.8%, 20.9% and 24.7% less for parallel, series and combined series-parallel configurations respectively as compared to equivalent VCRS (vapor compression refrigeration system) and after optimization, the same is further reduced by 8.1%, 8.5% and 4.7% respectively from the base value. Highlights: Comparative performance study of various integrated refrigeration systems. Modified Gouy–Stodola law shows quantitative difference in two exergy approaches. The total annual cost of integrated systems is reduced by optimization. Series and combined series-parallel systems are promising decarbonizing technology.